Indigenous Knowledge Integrated Biology Learning with Project-based Learning to Support Team Communication Skills - Fajar Adinugraha (Pro-Life, 2024)
Proficiency in team communication skills (TCS) is essential for academic achievement in higher education. Discussing socio-scientific issues that are also backed by indigenous knowledge, such as the environment and biodiversity, requires TCS. Nevertheless, there is a dearth of literature on the integration of indigenous knowledge or local wisdom into biology learning, particularly in the context of project-based learning (PBL) at the university level. The objective of this study is to delineate the process of indigenous knowledge integrated biology learning with project-based learning (IKIBL with PBL). Additionally, the aim is to ascertain the TCS score subsequent to treatment using IKIBL with PBL. The study, which employed classroom action research, involved 19 university students. The IKIBL with PBL is a series of activities that are aligned with the PBL methodology. These activities integrate research related to indigenous knowledge into learning. The results of this research were used to create an educational video. The results showed that there was an increase in the percentage of high categories in each learning cycle. Although there was no increase of high categories in Cycle 2, more than 75% of the students were in the high category. The most prominent aspect was closed-loop communication, followed by information sharing, and finally listening. TCS is needed as a requirement for 21st century learning and solving social science issues such as biodiversity and the environment.